CORRECTION OF ELDERLY AGE PEOPLE'S PSYCHO-PHYSIOLOGICAL CONDITION BY RECREATION MOTOR ACTIVITY - B.M. Mytskan; W. Cynarski; A.V. Fedoryuk; S.L. Popel'; T.S. Mytskan; N.O. Zemska (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to work out program of elderly age people's psycho-physiological condition correction by recreation-motor activity and test its effectiveness. Material: psycho-physiological condition and life quality of 50-65 years' age 155 teachers were analyzed with the help of two questionnaires. 50 teachers with low level of recreation activity were selected and divided into control and experimental group (25 persons in each). Results: main problems in organization of physical recreation have been determined. It became a base for working out and substantiation measures for intensification recreation activity of elderly age teachers. The basic principles of the worked out program are as follows: all year round physical exercises in natural geographic-climatic conditions; teachers' distribution by groups of recreation activity and level of motor activity. Conclusions: we have proved effectiveness of the offered measures, in respect of elderly age teachers' sleep and psycho-physiological state improvement.